2004
DOI: 10.1029/2004jd004873
|View full text |Cite
|
Sign up to set email alerts
|

Eleven‐year solar cycle signal throughout the lower atmosphere

Abstract: A statistically significant atmospheric signal, which represents the influence of solar radiation changes on our climate, is found in global data (1958–2003). Using a nonlinear, nonstationary time series analysis, called empirical mode decomposition, it is shown that atmospheric temperatures and geopotential heights are composed of five global oscillations and a trend. The fourth mode is synchronized with the 11‐year solar flux almost everywhere in the lower atmosphere. Statistical tests show that this signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…In this introductory section we briefly summarize results from other authors that found correlation between solar activity and physical parameters of the troposphere, notably the ground temperatures. Coughlin and Tung (2004) found an 11-year sun-correlated signal in the lower troposphere. Usoskin et al (2004bUsoskin et al ( , 2004c studied the correlation between solar activity and surface temperature over the last 1150 years and found a correlation coefficient of 0.7-0.8 with a significance level ranging between 94% and 98%.…”
Section: Introductionmentioning
confidence: 98%
“…In this introductory section we briefly summarize results from other authors that found correlation between solar activity and physical parameters of the troposphere, notably the ground temperatures. Coughlin and Tung (2004) found an 11-year sun-correlated signal in the lower troposphere. Usoskin et al (2004bUsoskin et al ( , 2004c studied the correlation between solar activity and surface temperature over the last 1150 years and found a correlation coefficient of 0.7-0.8 with a significance level ranging between 94% and 98%.…”
Section: Introductionmentioning
confidence: 98%
“…This section considers the multidecadal trends (e.g., Brönnimann et al 2007) rather than the great many reports of putative solar-cycle variations observed in the troposphere (e.g., Camp and Tung 2007;Coughlin 2004;Gleisner et al 2005). One reason why the global climate response timescales have recently become a consideration is the realisation that, since 1985, all the relevant solar outputs have been changing in the opposite direction to those needed to explain the rise in GMAST (Lockwood and Fröhlich 2007).…”
Section: Global Climate Responsementioning
confidence: 99%
“…Soukharev and Hood, 2006;Frame and Gray, 2010;Gray et al, 2013;Mitchell et al, 2014) used multiple linear regression to extract the solar signal and separate other climate phenomena like the QBO, the effect of aerosols, North Atlantic Oscillation (NAO), El Niño-Southern Oscillation (ENSO) or trend variability. Apart from this conventional method, it is possible to use alternative approaches to isolate and examine particular signal components, such as wavelet analysis (Pisoft et al, 2012(Pisoft et al, , 2013 or empirical mode decomposition (Coughlin and Tung, 2004). The nonlinear character of the climate system also suggests potential benefits from the application of fully nonlinear attribution techniques to study the properties…”
Section: A Kuchar Et Al: Solar Cycle In Current Reanalysesmentioning
confidence: 99%